Terson’s Syndrome with Roth Spot-Resembling Features and Third Nerve Palsy without Radiologically Diagnosed Subarachnoid Haemorrhage - Olga E. Makri; Iasonas K. Tsekouras; Stylianos N. Mastronikolis; Vasileios E. Panagiotopoulos; Constantine Constantoyannis; Constantinos D. Georgakopoulos (Vision)
We report an unusual case of pupil-involving third nerve palsy associated with Terson’s syndrome that resulted in the diagnosis of a right posterior communicating artery aneurysm. Interestingly, Terson’s syndrome presented with Roth spot-resembling features, accompanied by third nerve palsy in a patient without any disturbance of consciousness. To our knowledge, the association of Terson’s syndrome with third nerve palsy has not been described before in the absence of radiologically diagnosed subarachnoid haemorrhage. We present the case of a 48-year-old woman who presented in the Department of Emergencies of the University Hospital of Patras with right-sided complete-pupil-involving third nerve palsy combined with bilateral Terson’s syndrome. More precisely, fundoscopy revealed multiple scattered intra- and pre-retinal haemorrhages in both eyes, while some retinal haemorrhages had a white-centred pattern resembling Roth spots. Neurological examination revealed no nuchal rigidity or any other neurological signs. The Glasgow coma scale score was 15/15. A cerebral computed tomography angiography revealed a 5 mm aneurysm of the right posterior communicating artery and the patient underwent a microvascular clipping operation after craniotomy. The significant contribution of the ophthalmological consultation to the appropriate and timely diagnosis and management of a life-threatening condition is highlighted.